2014
DOI: 10.1007/s00404-014-3577-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated IGFBP-1 in predicting successful vaginal delivery in post-term pregnancy

Abstract: PurposeTo estimate whether phosphorylated IGFBP-1 (phIGFBP-1) in cervical secretion in term and post-term pregnancies can predict spontaneous onset of labor or vaginal delivery.MethodsA prospective cohort study of 167 women in singleton term and post-term pregnancies, was conducted at 1st Department of Obstetrics and Gynecology, Medical University of Warsaw, between 2013 and 2014. phIGFBP-1 test (Actim Partus Medix Biochemica), ultrasound cervix assessment and Bishop score were analyzed in the study group. Spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Our results are consistent with the study conducted by Kosinska-Kaczynska et al (7) who studied 167 women. IGFBP-1 test, TVUS-CL and Bishop score were studied in the study group where 67.5% of patients delivered vaginally and 32.5% had cesarean section.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with the study conducted by Kosinska-Kaczynska et al (7) who studied 167 women. IGFBP-1 test, TVUS-CL and Bishop score were studied in the study group where 67.5% of patients delivered vaginally and 32.5% had cesarean section.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Cheung et al . and Kosinska‐Kaczynska et al . found a positive association between cervical pIGFBP‐1 and vaginal delivery following induction of labor.…”
Section: Discussionmentioning
confidence: 77%
“…Among the three biomarkers of Premaquick, two biomarkers (native IGFBP1 and total IGFBP1) have never been evaluated for assessment of induction of labor. Previous studies have only tested phosphorylated IGFBP‐1 compared with Bishop score and or TVUS or TVUS compared with Bishop score, and very recent Cochrane systematic review by Ezebialu et al . indicated that direct comparisons between Bishop score and pIGFBP‐1 and IL‐6 for assessing preinduction cervical ripening among parturients at term gestations was yet to be carried out .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the combined use of ultrasonographic cervical length and a novel biochemical marker like the E3-to-E2 ratio could be a good predictor of successful induction of labor. Kosinska-Kaczynska et al [29] evaluated insulin-like growth factor binding protein-1 (IGFBP-1) in cervical secretion in term and postterm pregnancies can predict spontaneous onset of labor or successful vaginal delivery in pregnant women with induced labor. They found that the phosphorylated IGFBP-1 test may be a predictor of spontaneous onset of labor and successful vaginal delivery in postterm pregnancies.…”
Section: Discussionmentioning
confidence: 99%